Strategies for the Endoscopic Management and Post-Resection Treatment of Superficial Esophageal Squamous Cell Carcinoma - Hyun Ho Choi (Yong Chan Lee, 2024)
Endoscopic resection (ER) is preferred for treating superficial esophageal squamous cell carcinoma (SESCC) that has a low risk of lymph node metastasis; the preference is due to the technique's minimal invasiveness and having outcomes comparable to those of surgical resection, in suitable cases. Determining the appropriateness of ER requires a multidisciplinary review involving a pathological examination of the tumor's depth, size, and lymphovascular invasion following resection of a specimen. According to the Korean guidelines, no additional treatment is necessary after a complete en bloc resection of SESCC that lacks submucosal invasion and lymphovascular invasion. In cases of non-curative resection for tumors that exhibit submucosal invasion, lymphovascular invasion, or positive margins, additional treatment (e.g., esophagectomy or chemoradiotherapy) is recommended. Due to the uncertainty regarding which treatment is more effective, tailored therapy that is based on patient factors and tumor characteristics is needed to maximize patient long-term survival and improve quality of life.